RELEVANSI PENERAPAN KONSEP PENDIDIKAN ISLAM MENGGUNAKAN FILOSOFI IBNU KHALDUN DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Aina Rosyida (UIN ANTASARI BANJARMASIN, 2020)
The phenomenon of combining digital and internet technology with conventional industry is known as the era of industrial revolution 4.0, which has a big impact on all aspects of life. The measure of success in facing the industrial revolution 4.0 is Human Resources (HR). So that, education is a relevant way to deal with it. Islam requires to study and become an educated people. Therefore, researchers found the formulation of Islamic education has its own uniqueness with Ibn Khaldun's prominent ideas in terms of originality and beyond time. Based on this, the purpose of this research is to find out the relevance of the implementation of the concept of Islamic education which contains philosophy of Ibn Khaldun in facing the industrial revolution 4.0. The method used by the researcher is library research and described through qualitative - descriptive. To support the research, researcher uses two data sources namely primary data sources and secondary data sources. The technique of data collection is through library research, books, journals and references that support the research. The results showed that the concept of education that contained philosophy of Ibn Khaldun is relevant for dealing with the industrial revolution 4.0 with (1) development of proficiency (al-malakah or skill) (2) mastery of professional skills good thinking coaching. The conclusion of this study is that with the changing times that exist and the emergence of the latest innovations in education implicitly and explicitly have been designed in Islamic education.